10.47313 Pop Culture Through Lyrics: How Songs Reflect Social Trends - Yuliasari, Ria; Rika Virtianti; Ferdias Prihatna Sari (Pujangga, 2025)
This study explores how popular culture is reflected in the songs Anti-Hero by Taylor Swift, Happier Than Ever by Billie Eilish, and Traitor by Olivia Rodrigo. The research aims to identify which social trends are depicted in these songs and analyze their similarities and differences in reflecting societal concerns. Using a descriptive qualitative method, the study applies the framework of T.A. Writer, which identifies six key social trends in modern society: mental health awareness and reducing stigma, redefining family and relationships, digital detox and mindful technology use, individual activism and social responsibility, sustainable and ethical consumerism, and shifting work culture to remote and hybrid models. The findings reveal that not all six social trends are present in the selected songs. Each song reflects different aspects of societal change, with mental health issues and redefining relationships emerging as the most prominent themes. While Anti-Hero focuses on self-perception and emotional struggles, Happier Than Ever portrays personal growth after a toxic relationship, and Traitor reflects betrayal and emotional turmoil. The analysis highlights how pop music serves as a mirror of contemporary issues, particularly in the realms of mental health and interpersonal relationships. These songs resonate with audiences by providing an emotional connection to real-life struggles, reinforcing the role of music in shaping and reflecting cultural narratives. This research contributes to the understanding of music as an expression of social change and personal identity. Keywords: pop culture, song lyric, social trends